Abrasion resistance of sustainable green concrete containing waste tire rubber particles. (15th October 2016) - Thomas, Blessen Skariah; Kumar, Sanjeev; Mehra, Priyansha; Gupta, Ramesh Chandra; Joseph, Miquel; Csetenyi, Laszlo J.
Abstract: The development of new environmental friendly concretes such as rubberized concrete is being promoted due to the environmental problems created by the waste tire rubber. Every year millions of tires are discarded, thrown away or buried all over the world, representing a very serious threat to the ecology. In this study, we analyse the potential of waste tire rubber particles as a partial substitute for fine aggregates in normal strength and high strength cement concrete and the resistance to abrasion has been measured. Statistical Analysis was carried out to strengthen the results obtained from experiments. The results show that the use of tire rubber particles can improve the abrasion resistance of concrete, and this can ensure its applications in pavements, floors and concrete highways, or in places where there are abrasive forces between surfaces and moving objects.